The impact of digital payments on the velocity of money in the Chinese market - Yiling Chen (2021)
To study the impact of digital payments on the velocity of money circulation, this paper selects the velocity of money circulation at the M2 level in the Chinese market from FY2012 to 202112 quarters as the dependent variable, the size of digital payment transactions as the independent variable, and gross national product, inflation rate and opportunity cost of money as control variables. In terms of model selection, since the inflation rate and opportunity cost of money are monthly data, while the transaction size of digital payment and the circulation speed of money at the M2 level are quarterly data, the MIDAS series model is chosen to compare with the traditional OLS model, and it is found that MIDAS-PDL has the best fitting effect and prediction accuracy. Through the empirical results of the MIDAS-PDL model, we find that for the Chinese market, digital payments have a significant positive effect on the velocity of money circulation, in addition, inflation has a significant positive effect on the velocity of money circulation, while the opportunity cost of money has a significant negative effect on the velocity of money circulation.